Reasonable restrictions on the freedom of fishing in high seas marine protected areas from an international law perspective: an analysis - Wang, Yong; Pan, Xin (Frontiers in Marine Science, 2023)
With the development of marine protected areas (MPAs) on the high seas in the international community and an international agreement protecting biodiversity beyond national jurisdiction, how to reasonably restrict the freedom of fishing in the high seas MPAs has become a controversial issue in theory and in practice. This article will use doctrinal research method. It will discuss existing provisions regarding restricting the freedom of fishing on the high seas including the high seas MPAs. These provisions have been codified in international treaties, international resolutions, and international soft law. In addition, since regional fisheries management organizations (RFMOs) also take part in fishery management in the high seas MPAs, this article will refer to measures of relevant RFMOs to discuss how restriction is going in terms of the freedom of fish in the high seas MPAs. This article finds that the fishing-restriction measures stipulated in international documents represented by the United Nations Convention on the Law of the Sea are too general. In addition, some treaties do not address certain issues of restricting fishing methods by non-contracting parties. Therefore, these treaties are limited. The fishing practices of the four high seas MPAs that have been established by the international community reveals the establishment of several reasonable fishing restrictions. However, their shortcomings are evident. From the perspective of international law, it is important to improve the principle of reasonably restricting the freedom of fishing in MPAs on the high seas based on practice and positive law while proceeding steadily. Moreover, restriction measures cannot be too broad or narrow. Specifically, we should continue to develop mechanisms such as exceptions, ways of restricting fishing, advocacy provisions for non- contracting parties and measures to strengthen international information exchange.